Political Finance: The Case of Global Equity Markets and US Political Parties - Lim, Jia Cheng (2010)
Following the financial meltdown in 2007 and the collapse of the government of Iceland, one could only conclude that politics and equity markets are ultimately corelated. And as the world turn to the Democratic Party under Obama’s administration to turn the tides of the global economy (Chossudovsky, 2008), the academia has to further pursue the understanding of the interplay between politics and financial markets, especially in global equity markets. This study first examines the global equity market and US political linkages through incorporating the four year US election cycle into a study of global equity market linkages. This study finds that as markets become increasingly deregulated, the influence of the US politics in global equity markets increases. For the purpose of a more cohesive view on the market, global equity markets have been split to three categories namely large developed countries, large developing countries (rising markets) and small developed countries. This study provides empirical evidence, through the application of Johansen Juselius cointegration tests and granger causality in VAR and VECM models that global markets are inevitably, subject to the influence of US politics. This study follows by examining short-term US presidential anomalies using an adapted version of the Riley and Lukesetich (1980) event study model and provides empirical evidence on the persistence of the Wall Street Folklore that was never critically studied since several decades ago. Several key findings relevant to the very conceptual framework of neoclassical finance emerged from the empirical evidence was further discussed through this study.